The genus Cecyrina Walker, 1867, with the description of two new species (Hemiptera: Pentatomidae: Asopinae) - Zhao, Qing; Bu, Wen-Jun; Liu, Guo-Qing (Zootaxa, 2016)
In this paper, three species of the genus Cecyrina Walker are reported. Of these, the type species C. platyrhinoides Walker, 1867 is the only member of the genus previously recorded. Cecyrina flata sp. nov. and C. rubra sp. nov. are described as new to science. Illustrations of the male and female genitalic structures, the dorsal view of the head, the ventral view of the abdomen, and photographs of the adult dorsal and ventral habitus are provided. A key to the males of the genus is also provided to assist in future identification. The type specimens are deposited in the Institute of Entomology, Nankai University, Tianjin, China, except where noted.